A prospective community-based study of stroke in Germany - The Erlangen Stroke Project (ESPro): Incidence and case fatality at 1, 3, and 12 months - Kolominsky-Rabas, Peter; Sarti, Cinzia; Heuschmann, Peter U.; Graf, Christian; Siemonsen, Sven; Neundörfer, Bernhard; Katalinic, Alexandar; Lang, Erich; Gaßmann, Karl-Günter; Von Stockert, Theodor Ritter (Stroke, 1998)
Background and Purpose - In Germany, basic data on stroke morbidity are lacking. If a population-based register in former East Germany is excluded, only routine mortality statistics have thus far provided information on epidemiology of stroke. Therefore, a population-based register of stroke was set up in Southern Germany to determine incidence and case fatality in a defined German population. Methods - The Erlangen Stroke Project (ESPro) is a prospective community-based study among the 101 450 residents of the city of Erlangen, Bavaria, Germany. Standard definitions and overlapping case- finding methods were used to identify all cases of first-ever stroke in all age-groups, occurring in the 2 years of registration (April 1, 1994, to March 31, 1996). All identified cases of first-ever strokes were followed up at 3 and 12 months from onset. Results - During 2 years of registration, 354 first-ever-in-a-lifetime strokes (FELS) were registered. The diagnosis and stroke type were confirmed by CT scan in 95% of cases. Fifty-one percent of all FELS occurred in the age group ≥75 years of age. The crude annual incidence rate was 1.74 per 1000 (1.47 for men and 2.01 for women). After age-adjustment to the European population, the incidence rate was 1.34 per 1000 (1.48 for men and 1.25 for women). The annual crude incidence rate of cerebral infarction was 1.37/1000, intracerebral hemorrhage 0.24/1000, subarachnoid hemorrhage 0.06/1000, and unspecified stroke 0.08/1000. Overall case fatality at 28 days was 19.4%, at 3 months it was 28.5%, and at 1 year 37.3%. Conclusions - The first prospective community-based stroke register including all age groups in Germany revealed incidence rates of stroke similar to those reported from other population-based studies in western industrialized countries, but lower than that observed in former East Germany.
Created from Fastlane, Scopus look-up
Keywords: Epidemiology; Germany; Incidence; Mortality; Prognosis

Association between infection with Helicobacter pylori and Chlamydia pneumoniae and risk of ischemic stroke subtypes: Results from a population-based case-control study - Maass, Matthias; Faller, Gerhard; Gesslein, Markus; Neureiter, Daniel; Neundörfer, Bernhard; Craiovan, Benjamin; Beck, Georg; Kolominsky-Rabas, Peter; Heuschmann, Peter U. (2001)
Background and Purpose - Helicobacter pylori and Chlamydia pneumoniae have been associated epidemiologically and pathogenetically with coronary atherosclerosis. However, population-based data on chronic infection and stroke are lacking. Therefore, we investigated the association of both bacterial pathogens and ischemic stroke subtypes in a population-based case-control study. Methods - Patients with first ischemic stroke in the population-based Erlangen Stroke Project were collected as cases. Neighborhood controls were drawn from the study population, matched for age, sex, and place of residence. IgG antibodies to H pylori were measured by enzyme immunoassay, and IgG antibodies to C pneumoniae were measured by microimmunofluorescence technique. Conditional logistic regression was used. Analyses were stratified for etiologic stroke subtypes according to Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. Results - A total of 145 case and 260 control subjects were included. Chronic H pylori infection was associated with a higher risk of stroke caused by small-artery occlusion (adjusted odds ratio, 3.31; 95% CI, 1.15 to 9.56) and a lower risk of cardioembolic stroke (adjusted odds ratio, 0.21; 95% CI, 0.06 to 0.71). Overall, elevated H pylori as well as elevated C pneumoniae antibodies were not associated with ischemic stroke. Conclusions - Our population-based study does not provide evidence of any strong association between the immune response to C pneumoniae as a marker of prior infection and ischemic stroke. Further studies are required to reveal the role of chronic H pylori infection as an independent risk factor for the subgroup small-artery occlusion.
Created from Fastlane, Scopus look-up
Keywords: Chlamydia pneumoniae; Helicobacter pylori; Seroepidemiologic studies; Stroke

Epidemiology of ischemic stroke subtypes according to TOAST criteria: Incidence, recurrence, and long-term survival in ischemic stroke subtypes: A population-based study - Kolominsky-Rabas, Peter; Weber, Margarete; Gefeller, Olaf; Neundörfer, Bernhard; Heuschmann, Peter U. (Stroke, 2001)
Background and Purpose - The purpose of this study was to determine the incidence, recurrence, and long-term survival rates of ischemic stroke subtypes by a mechanism-based classification scheme (Trial of ORG 10172 in Acute Stroke Treatment, or TOAST). Methods - We identified all 583 residents of the city of Erlangen, Bavaria, Germany, with a first ischemic stroke between 1994 and 1998. Multiple overlapping sources of information were used to ensure completeness of case ascertainment. The cause of ischemic stroke was classified according to the TOAST criteria. Patients were followed up at 3 months and 1 and 2 years after stroke onset. Results - The age-standardized incidence rates for the European population (per 100 000) regarding ischemic stroke subtypes were as follows: cardioembolism, 30.2 (95% CI 25.6 to 35.7); small-artery occlusion, 25.8 (95% CI 21.5 to 30.9); and large-artery atherosclerosis, 15.3 (95% CI 12 to 19.3). When age-adjusted to the European population, the incidence rate for large-artery atherosclerosis was more than twice as high for men than for women (23.6/100 000 versus 9.2/100 000). Two years after onset, patients in the small-artery occlusion subgroup were 3 times more likely to be alive than those with cardioembolism. Ischemic stroke subtype according to the TOAST criteria was a significant predictor for long-term survival, whereas subtype was not a significant predictor of long-term recurrence up to 2 years, both before and after adjustment for age and sex. Conclusions - Epidemiological observational studies that possess wide access to appropriate diagnostic technologies and apply standardized etiologic classifications provide a much better understanding of underlying risk factors for initial stroke, recurrence, and mortality.
Created from Fastlane, Scopus look-up
Keywords: Epidemiology; Incidence; Recurrence; Stroke classification; Survival

Lifetime cost of ischemic stroke in Germany: Results and National Projections From a population-based stroke registry. The Erlangen Stroke Project - Kolominsky-Rabas, Peter; Heuschmann, Peter; Marschall, Daniela; Emmert, Martin; Baltzer, Nikoline; Neundörfer, Bernhard; Schöffski, Oliver; Krobot, Karl J. (Stroke, 2006)
Background and Purpose - The number of stroke patients and the healthcare costs of strokes are expected to rise. The objective of this study was to determine the direct costs of first ischemic stroke and to estimate the expected increase in costs in Germany. Methods - An incidence-based, bottom-up, direct-cost-of-ischemic-stroke study from the third-party payer's perspective was performed, incorporating 10-year survival data and 5-year resource use data from the Erlangen Stroke Registry. Discounted lifetime year 2004 costs per case were obtained and applied to the expected age and sex evolution of the German resident population in the period 2006 to 2025. Results - The overall cost per first-year survivor of first-ever ischemic stroke was estimated to be 18 517 euros (EUR). Rehabilitation accounted for 37% of this cost, whereas in subsequent years outpatient care was the major cost driver. Discounted lifetime cost per case was 43 129 EUR overall and was higher in men (45 549 EUR) than in women (41 304 EUR). National projections for the period 2006 to 2025 showed 1.5 million and 1.9 million new cases of ischemic stroke in men and women, respectively, at a present value of 51.5 and 57.1 billion EUR, respectively. Conclusions - The number of stroke patients and the healthcare costs of strokes in Germany will rise continuously until the year 2025. Therefore, stroke prevention and reduction of stroke-related disability should be made priorities in health planning policies. © 2006 American Heart Association, Inc.
WiSo-Import:2015-03-26:4363
Keywords: Cost of illness; Costs and cost analysis; Ischemic stroke; Resource use; Stroke